2009
DOI: 10.1177/0095798408329941
|View full text |Cite
|
Sign up to set email alerts
|

Stigma, Culture, and HIV and AIDS in the Western Cape, South Africa: An Application of the PEN-3 Cultural Model for Community-Based Research

Abstract: HIV- and AIDS-related stigma has been reported to be a major factor contributing to the spread of HIV. In this study, the authors explore the meaning of stigma and its impact on HIV and AIDS in South African families and health care centers. They conducted focus group and key informant interviews among African and Colored populations in Khayelitsha, Gugulethu, and Mitchell’s Plain in the Western Cape province. The audio-recorded interviews were transcribed and coded using NVivo. Using the PEN-3 cultural model,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 79 publications
(89 citation statements)
references
References 37 publications
1
88
0
Order By: Relevance
“…First, my finding of a Tanzanian cultural context of HIV stigma and discrimination is consistent with findings of a high prevalence of HIV stigma and discrimination in African communities (e.g., Petros et al, 2006;Airhihenbuwa et al, 2009;Okoror et al, 2014). For example, drawing on a focus group study of women living with HIV/AIDS in South Africa to explore the experience of stigma in healthcare settings, Okoror et al (2014) found stigmatizing practices such as specific file colors being used for HIV-positive patients and sections of the healthcare setting reserved only for PLWHA.…”
Section: Discussionsupporting
confidence: 87%
“…First, my finding of a Tanzanian cultural context of HIV stigma and discrimination is consistent with findings of a high prevalence of HIV stigma and discrimination in African communities (e.g., Petros et al, 2006;Airhihenbuwa et al, 2009;Okoror et al, 2014). For example, drawing on a focus group study of women living with HIV/AIDS in South Africa to explore the experience of stigma in healthcare settings, Okoror et al (2014) found stigmatizing practices such as specific file colors being used for HIV-positive patients and sections of the healthcare setting reserved only for PLWHA.…”
Section: Discussionsupporting
confidence: 87%
“…This study is part of an NIH-funded, capacity-building HIV and AIDS stigma project in South Africa for disadvantaged, underserved Black post-graduate students at the University of the Western Cape and the University of Limpopo. 1 Focus group discussions included home-based caregivers in the Limpopo Province of South Africa. The ethics committee of The Pennsylvania State University and Human Sciences Research Council in South Africa reviewed and approved this study.…”
Section: Methodsmentioning
confidence: 99%
“…The project's goal was to examine contextual factors that may contribute to HIV-and AIDS-related stigma in the community in general, and in the family and health care settings in particular. Focus groups were conducted with key informants to explore HIV and AIDS stigma (Airhihenbuwa et al, 2009;Iwelunmor et al, 2010). Focus groups are ideal in this setting as they facilitate open discussions in ways that allow participants to express their views, including the opportunity to elaborate on comments made by members (Iwelunmor et al, 2010).…”
Section: Study Area and Samplingmentioning
confidence: 99%